Data at the municipality level - Mabille, Geraldine; Stien, Audun; Tveraa, Torkild; Mysterud, Atle; Brøseth, Henrik; Linnell, John D. C. (Dryad Digital Repository, 2015)
The origin of the different variables is given in the article. The column headings refer to the variable names used in the article. See legends in tables 2, 3 and 4 for details on the units used.